China's Access to Gwadar Port: Strategic Implications and Options for India. (2nd January 2017) - Conrad, Ms. Portia B.
ABSTRACT: Since the establishment of diplomatic relations in 1951, Pakistan's desire for strategic parity with India and China's efforts to propel Pakistan as a strategic balancer to India have been the overarching factors for the emergence of a security centric Sino–Pak relationship. Over the years, it has diversified into an economic-centric relationship. Although military and technological transactions continue to dominate the economic relationship, China began gradually pledging increased investment in Pakistan's economy and infrastructure. China became the primary investor for building the Gwadar deep-sea port in 2002. Both sides signed a free trade agreement and agreed to link China's rail network to Gwadar Port through the Karakoram Highway in 2008. The commitment to develop Gwadar Port is a good indicator of the steady expansion of Chinese maritime interests and strategic influence in India's neighbourhood. This paper attempts to analyse the significance and implications of the development of Gwadar Port for Pakistan, India and the region as a whole.